2016
DOI: 10.1515/tvsbses-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicological Tests - Applications of Foils Based on Graphene (Graphene Oxide)

Abstract: Abstract:This paper discusses the problematics of phytotoxicity of chemicals. It mainly focuses on the phytotoxicity of nanomaterials made of graphene. It describes phytotoxicological tests performed with foils from materials belonging to the graphene family. It also describes testing the infl uence of plants on these fi lms. Furthermore, the paper discusses the issues of mutual infl uence between plants and tested nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Chen et al [42] also found that GOs inhibited the germination of wheat, and at high concentrations, GOs accumulated in the root system, inducing oxidative stress. The effect of nGO-based materials on S. alba was studied by Roupcová et al [43]. They found that the germination of S. alba seeds was inhibited when cultivated on nGO foils, but outside the foils, it was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [42] also found that GOs inhibited the germination of wheat, and at high concentrations, GOs accumulated in the root system, inducing oxidative stress. The effect of nGO-based materials on S. alba was studied by Roupcová et al [43]. They found that the germination of S. alba seeds was inhibited when cultivated on nGO foils, but outside the foils, it was enhanced.…”
Section: Discussionmentioning
confidence: 99%